Interview-Based Qualitative Descriptive Study on Risk Factors of School Withdrawal among Elementary School Children - Sachiko Înoue (MDPI AG, 2022)
With increasing school refusal among elementary school children, we qualitatively examined the associated factors. Elementary school teachers underwent semi-structured interviews, and the data generated were analyzed using SCAT. We conducted interviews with 27 teachers (18 men, nine women) responsible for children refusing to attend school. We analyzed verbatim transcripts of the interviews and abstracted six constructs for school refusal: underdeveloped interpersonal skills; families having difficulty in supporting their children to attend school; low self-esteem; diverse views on school refusal; tenuous relationships among local community members; and an environment where games and media are easily accessible. Children refusing to attend school may be unable to relate well to other people owing to underdeveloped interpersonal skills, and they may have low self-esteem. Regarding the home environment of children who are not positive about school life, living in families having difficulty in supporting their children to attend school may make the children less likely to do so. Because of tenuous relationships with local community members, there has been a decline in the involvement of people around children other than family members in encouraging school attendance. Recently, diverse views on school refusal have been accepted; increasingly, parents and children are likely to choose to spend time outside school. An environment in which games and media are easily accessible may make it easy to relate to other people without attending school, undermining the need for school attendance.